Cost effectiveness and optimal control analysis for bimodal pneumonia dynamics with the effect of children's breastfeeding - Legesse, Fekadu Mosisa; Rao, Koya Purnachandra; Keno, Temesgen Duressa (Frontiers in Applied Mathematics and Statistics, 2023)
For full guidelines regarding your manuscript please refer to Author Guidelines.The global impact of exclusive versus inclusive nursing on particular baby mortalities and morbidities from conception to six months is examined in this study. Exclusive breastfeeding practises are more crucial and effective in preventing illness outbreaks when there is no access to appropriate medications or vaccinations. This study also takes optimal control theory into account, applying it to a system of differential equations that uses Pontryagin's Maximum Principle to describe a bimodal pneumonia transmission behaviour in a vulnerable compartment. The proposed pneumonia transmission model was then updated to include two control variables.These include preventing illness exposure in susceptible children through the use of various preventative measures and treating infected children through the use of antibiotics, hospital care, and other treatments. If the threshold number (R 0 ) is less than one, then treatment and prevention rates are increased, and disease will be wiped out of the population. But when (R 0 ) is greater than one, then the disease persists in the population, which indicates prevention and treatment rates are low.To evaluate the cost-effectiveness of all potential control techniques and their combinations, the incremental cost-effectiveness ratio (ICER) was determined. The simulation results of the identified model show that the interventions of prevention and treatment scenarios were most successful in eradicating the dynamics of the pneumonia disease's propagation during the epidemic, but they were ineffective from a cost-savings perspective. Therefore, limiting pneumonia transmission to prevention alone during an outbreak is the most economical course of action.